Factors influencing customer behavioral intention to revisit Restoran Melayu Melaka - Nur Fuad, Nur Faris (2019)
Dinescape seems to be accepted as a fundamental factor that will influence customer behavioural intentions; however, it has been often being ignored in restaurant service quality and satisfaction studies. The primary objective of this study was to investigate the factor that influencing customer behavioural intentions to revisit Restoran Melayu Melaka. This study also attempted to investigate the improvement of Dinescape towards customer behavioural intentions with a structural equation modelling technique; this study shows that overall Dinescape quality significantly affects customer behavioural intentions. Subsequent regression analyses demonstrated that Dinescape influence customer behavioural intentions through the quality that the restaurant serve to their customer. Thus, managers should pay attention to the key Dinescape attributes that elicit customer behavioural intentions and enhance return visits in the restaurant business.